(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
The Second World War inflicted profound economic and social disruptions on the Soviet Union; however, the central government emphasized that post-war recovery would be achieved through the nation’s internal resources and collective efforts. In the subsequent reconstruction period, extensive policies were implemented to restore the economy and expand agricultural production. A central aspect of this strategy was the reclamation and development of new agricultural lands across the Union republics, with a particular focus on strengthening cotton cultivation as a key raw material base. In Uzbekistan, and notably in the Andizhan region, substantial areas of land were brought under cultivation, leading to a significant increase in cotton output. This expansion not only contributed to regional economic growth but also played a critical role in supplying the Soviet textile industry. The land development initiatives in Andizhan thus illustrate the broader dynamics of Soviet agrarian policy, serving as an important element in post-war reconstruction and the modernization of the national economy.